Mitigating Urban Heat Islands in the Global South: Data-driven Approach for Effective Cooling Strategies - Chakrabortty R.; Pramanik M.; Hasan M.M.; Halder B.; Pande C.B.; Moharir K.N.; Zhran M. (Springer Science and Business Media Deutschland GmbH, 2025)
The Urban Heat Islands (UHI) phenomenon presents a pressing concern in many megacities worldwide, demanding urgent attention for proper mitigation and sustainable development. In regions like Bangkok, where population pressures and extreme climate conditions exacerbate the issue, addressing heat islands becomes critical. While previous studies have primarily focused on Land Surface Temperature (LST) assessments, comprehensive heat mitigation strategies remain largely unexplored. Therefore, there is a critical need to quantify cooling capacity and heat mitigation for effective urban planning. This study utilized the 'urban cooling model' to assess heat mitigation measures using parameters such as albedo, the cooling capacity of parks, evapotranspiration, green area, green area sum, UHI cooling effect, reference end of transmission, shade, air temperature, air temperature nomix, and Wet Bulb Globe Temperature (WBGT) across different land use zones. The model generates insights into cooling capacity and heat mitigation indices. The maximum and minimum mean cooling capacities were found in Ban Phaeo (0.20) and Khlong Luang (0.05) provinces, respectively. Additionally, the maximum and minimum heat mitigation were observed in Bang Bo (0.11) and Bang Bua (0.05). The analyses between heat mitigation and intermediate variables of the urban cooling model elucidate their relationships, aiding in the optimal determination of cooling capacity and heat mitigation indices. This study highlights the importance of strategic urban cooling strategies in Bangkok to enhance sustainable urban development. Graphical Abstract: (Figure presented.). ? King Abdulaziz University and Springer Nature Switzerland AG 2024.